AI-DRIVEN DIGITAL TRANSFORMATION OF MSMES: LEVERAGING GOOGLE VEO 3 FOR STRATEGIC CONTENT OPTIMIZATION IN E-COMMERCE - Fauzi, Fauzi; Muslihudin, Muhamad; Ramadian, Sabda Iman (STMIK Pringsewu, 2025)
Digital transformation has become an essential requirement for Micro, Small, and Medium Enterprises (MSMEs) to remain competitive in the e-commerce era. However, many MSMEs struggle to produce high-quality visual content that effectively attracts online consumers. This study aims to examine the role of Google VEO 3, an AI-based visual generation tool, in optimizing digital content strategies among three MSMEs in Pringsewu: Kripik Yado, Keripik Barokah, and Dianshop. Using a qualitative descriptive method through observation, interviews, and content creation simulations, the study reveals that AI implementation significantly enhances content quality, audience engagement, and product visibility, leading to improved sales performance. The findings highlight that Google VEO 3 is an accessible and cost-effective innovation that fosters digital literacy and confidence among MSMEs. The novelty of this research lies in its empirical analysis of AI-driven visual tools as catalysts for sustainable and inclusive MSME digital transformation